The allocation of authority under limited liability - Kerstin Puschke (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
Authority is modelled as the right to undertake a non-contractible decision in a joint project. We show that the allocation of authority depends on bargaining power and differences in both parties cost functions. The decision-maker is assumed to exert an externality on the other parties. Overall surplus is shared according to generalized Nash bargaining. Under limited liability, the agent with the larger cost parameter receives authority if the agents' cost parameters are very different. If the agents have similar cost parameters, bargaining power determines the allocation of authority. Possible applications include the introduction of a new product.
Keywords: D23; L22; L24; 330; Authority; Decision Rights; Incomplete Contracts; Autorität; Kooperation; Beschränkte Haftung; Verhandlungstheorie; Theorie